The populist turn in EU politics and the intermediary role of civil society organisations. Issue 4 (8th August 2021) - Ruzza, Carlo; Sanchez Salgado, Rosa
ABSTRACT: The introduction to this special issue identifies an analytical and empirical gap in studies on European civil society organisations (CSOs) in the wake of the rise of populism. It explains how different contributions address these gaps. To this end, it first provides a definition of the main terms, including populism and anti-populism. It reconsiders assumptions regarding the role of CSOs and social movements as agents of European democratisation and legitimation. The main argument is that the populist turn has led to significant changes regarding the role of CSOs in the EU policy process. These changes are visible in three different but interrelated ways: the relations between European institutions and CSOs, the changes in CSOs goals and strategies, and the changes in the patterns of interaction between CSOs and populist groups. The final part of the introduction gives a brief overview of the contributions to this special issue and highlights how they provide further insights into the overall topic of relations between the EU and CSOs.